Detection of hemoplasma and Bartonella species and co-infection with retroviruses in cats subjected to a spaying/neutering program in Jaboticabal, SP, Brazil - Bortoli, Caroline Plácidi de [UNESP]; André, Marcos Rogério [UNESP]; Seki, Meire Christina [UNESP]; Pinto, Aramis Augusto [UNESP]; Machado, Saulo de Tarso Zacarias [UNESP]; Machado, Rosangela Zacarias [UNESP] (Colégio Brasileiro de Parasitologia Veterinária, 2012)
Micoplasmas hemotróficos e espécies de Bartonella são importantes patógenos que circulam entre gatos e hospedeiros invertebrados, causando ocasionalmente doenças no homem. Apesar disto, poucos são os estudos acerca da ocorrência destes agentes entre gatos no Brasil. O presente estudo objetivou detectar o DNA de hemoplasmas e Bartonella sp. pela PCR e sequenciamento. Antígeno de FIV e anticorpos anti-FeLV foram estudados utilizando um kit comercial, em amostras de sangue e soro, respectivamente, de 46 gatos amostrados em uma campanha de castração em Jaboticabal, SP. Três gatos (6,5%) foram positivos para hemoplasmas: dois (4,3%) para 'Candidatus M. haemominutum' e um (2,2%) para M. haemofelis and 'Candidatus M. turicensis'. Um dos gatos positivos para 'Candidatus M. haemominutum' mostrou-se também positivo na detecção de antígeno de FeLV e de anticorpos para FIV. Dois (4,3%) gatos mostraram-se positivos para B. henselae, sendo que um deles também se mostrou positivo para antígeno de FeLV. Oito gatos (17,4%) foram positivos para FeLV, e apenas um gato mostrou anticorpos anti-FIV. Bartonella sp. e hemoplasmas associados à infecção por retrovírus podem circular entre gatos aparentemente saudáveis.

Hemotrophic mycoplasmas and Bartonella species are important pathogens that circulate between cats and invertebrate hosts, occasionally causing diseases in humans. Nevertheless, there are few reports on occurrences of these agents in cats in Brazil. The present study aimed to detect the presence of hemoplasma and Bartonella DNA by means of PCR and sequencing. FIV antigens and anti-FeLV antibodies, were studied by using a commercial kit on blood and serum samples, respectively, among 46 cats that were sampled during a spaying/neutering campaign conducted in Jaboticabal, SP. Three (6.5%) cats were positive for hemoplasmas: two (4.3%) for 'Candidatus M. haemominutum' and one (2.2%) for both M. haemofelis and 'Candidatus M. turicensis'. One of the two 'Candidatus M. haemominutum'-infected cats was also positive for FeLV antigens and showed antibodies for FIV. Two cats (4.3%) were positive for B. henselae. One of them was also positive for FeLV antigens. Eight cats (17.4%) were positive for FeLV, and just one (2.2%) showed anti-FIV antibodies. Bartonella species and hemoplasmas associated with infection due to retroviruses can circulate among apparently healthy cats.
Detecção de hemoplasmas e Bartonella sp. e co-infecção com retrovírus em gatos submetidos a um programa de castração/esterilização em Jaboticabal, SP, Brasil
Keywords: Hemotrophic mycoplasmas; Bartonella henselae; FIV; FeLV; Cat; Micoplasmas hemotróficos; Bartonella henselae; FIV; FeLV; Gatos